Applying a new version of the Brazilian-Portuguese UPSIT smell test in Brazil - Laura Silveira‐Moriyama; Adriana Medeiros Sales de Azevêdo; Ronald Ranvaud; Egberto Reis Barbosa; Richard L. Doty; Andrew J. Lees (2010)
Standardized olfactory tests are now available to quantitatively assess disorders of olfaction. A Brazilian-Portuguese version of the University of Pennsylvania Smell Identification Test (UPSIT) is currently being developed specifically for the Brazilian population. The most recent Brazilian-Portuguese version of the UPSIT (UPSIT-Br2) was administered to 88 Brazilian subjects who had no history of neurological or otorhinolaryngological disease. UPSIT-Br2 scores decreased with age, were lower in men than in women, and were lower in subjects with lower income. The degree to which the poorer performance of subjects with lower socio-economic status reflects lack of familiarity with test items is not known. Although this version of the UPSIT provides a sensitive and useful test of smell function for the Brazilian population, a revision of some test items is needed to achieve comparable norms to those found using the North American UPSIT in the United States.